Kandungan Kimia, Fisik Dan Lama Simpan Buah Sawo (Achras Zapota L.) Dalam Penyimpanan Metode Mas - Jasman, Andri; Tamrin, Tamrin (Jurnal Agricultural Biosystem Engineering, 2025)
Sapodilla fruit is climacteric, after being harvested, the sapodilla fruit still undergoes a metabolic process until decay occurs. This study aims to determine the effect of temperature and the effect of different CO2, O2 compositions on changes in total dissolved solids (TDS) and total acid, physical (hardness) and storage time of sapodilla fruit in MAS (Modified Atmosphere Storage) storage. Research by varying the concentration of CO2, and O2 and N2 in the storage room. The results showed that the respiration rate was faster at room temperature (27ºC) with a CO2 gas composition of 3% and O2 8% compared to low temperatures and other gas compositions. Changes in TDS and total acid at a temperature of 12ºC were more regular with an increase in TDS and a decrease in total acid at a CO2 composition of 1% and O2 gas concentrations of 2%, 4% and 8% compared to other storage temperatures and CO2 and O2 compositions. Changes in hardness level at cold temperature 12ºC decrease in hardness level can be slowed down with CO2 composition 1%-2% and O2 2% compared to other temperatures and CO2 and O2 compositions. Storage using modified atmosphere can extend the shelf life of sapodilla fruit up to 20 days with atmospheric composition of CO2 1% and O2 8% with storage temperature 12ºC. Keywords: Hardness, respiration, Sapodilla, Shelf life, TDS.